(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
The Stile, Suzuki, Neighs, Kumara, and Hayami reactions also need an organometallic component in addition to a halide or pseudohalide (Sn, B, Zn, Mg, and Si). The 2010 Nobel Prize in Chemistry was shared by Richard F. Heck, Eiichi Neighs, and Akira Suzuki. Due to the tremendous impact that these interactions had on the creation of chemical compounds, natural products, and medical uses, this happened. Since Pd-catalyzed crosscoupling reactions take place at reasonably tolerant conditions, most functional groups may take part in them. The three basic steps of I oxidative addition, II reinstallation, and III reductive elimination make up the bulk of the processes. Base-modified nucleosides may be created via a number of different transition metal-catalyzed methods, which can then be broken down into the five main groups mentioned above. Each of the first two strategies involves some kind of cross-coupling between two active components. The first strategy combines organometallics with halo (or triflate) modified nucleoside bases, while the second technique combines metal-activated nucleoside bases with halides (Path b). These strategies have been well studied, yet the paper skips over the results. Heterocyclic scaffolds are now more crucial than ever in the manufacture of pharmaceuticals, agrochemicals, natural goods, and pharmaceutical active components. Organic cyclic scaffolds known as homocyclic compounds include at least one heteroatom, most often a nitrogen, oxygen, or sulphur atom. Heterocyclic compounds are also known as heterocycles. On the other hand, it is also known that heteroatoms built of heterocycles exist.